CHARACTERIZATION OF RESIDENTIAL ORGANIC WASTE DIGESTED AND VIABILITY OF USE IN IRRIGATED AGRICULTURE - Machado, Letícia Thália Silva [UNESP]; Leroy, Karl Auguste [UNESP]; Oliveira, Kassandra Sussi Mustafé [UNESP]; Sánchez Román, Rodrigo Máximo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2023)
Digestate obtained through anaerobic digestion can be beneficial in agricultural production, for this, it is important to know their properties and characteristics beforehand. The objective of this study was to characterize the digestate obtained from anaerobic treatment of food waste and evaluate the feasibility of its use in localized irrigation. A commercial biodigester (HomeBiogas 2.0) was used for this work and operated during 8 months (from april to december/2021). The digestate was evaluated for its physical-chemical and biological properties. Digestate presented interesting chemical elements for agricultural use, such as N, P, K, Ca, Mg, Cu, Fe, Mn, and Zn, as well as a high organic load. Additionally, the digestate presented acceptable microbiological sanity for agricultural application. However, the levels of Fe, dissolved solids, and suspended solids were above the recommended values for use in localized irrigation systems. Therefore, it is recommended to treat the digestate before applying it through this irrigation system. It can be concluded that if the digestate is used in accordance with professional guidelines, it can generate benefits in agricultural production, contributing as a source of nutrients for plants and organic matter for the soil.
CARACTERIZAÇÃO DE DIGESTATO DE RESÍDUOS ORGÂNICOS RESIDENCIAIS E VIABILIDADE DE USO NA AGRICULTURA IRRIGADA
Keywords: anaerobic digestion; biodigester; biofertilizer; HomeBiogas